2022
DOI: 10.1109/ojits.2022.3224677
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Takeover Time Budget Based on Analysis of Driver Behavior

Abstract: An automated driving system notifies a fallback-ready human driver to resume driving when critical operational and functional limits have been or are about to be exceeded. The point between notification and critical limit is the time budget. Previous studies indicate that interdependencies exist between takeover variables and the time budget leading to performance variations and sometimes accidents. It is known that drivers may delay or respond inadequately depending on the time budget. This contribution focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…More specifically, Reicherts et al [3] used naturalistic driving studies to identify vehicle dynamics. Tanshi and Söffker [4] proposed a method for determining the takeover time budget based on the analysis of driver behavior.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Reicherts et al [3] used naturalistic driving studies to identify vehicle dynamics. Tanshi and Söffker [4] proposed a method for determining the takeover time budget based on the analysis of driver behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The load types corresponding to the five non-driving related tasks are shown in Table 1. The TOR has been shown to be a determinant of driver take-over performance [35]. It has been shown that too long of a TOR causes the driver to try to first confirm a dangerous situation before taking over, thus prolonging the driving reaction time, while too short of a TOR is not enough to ensure the safety of the take-over.…”
mentioning
confidence: 99%